Noor-Eesti antifuturismist.On the Anti-Futurism of Young Estonia - Virve Sarapik (Methis: Studia Humaniora Estonica, 2008)
Young Estonia persists in Estonian cultural memory as a movement of renewal, among other factors through its impetus to the development of urban culture. This article undertakes to juxtapose Young Estonia’s efforts at cultural renewal, its rhetoric of the future, and futurism as a cultural phenomenon. (As such, futurism was vitally engaged with contemporary urban culture, industry, and technology.) Four parameters serve as points of departure: (1) Young Estonia’s rhetoric of the new and the future. Though specific about what they rejected, Young Estonia’s texts do not outline a clear vision of the future. Frequently used key words for what they opposed included German- or Russian-mindedness, a people in servitude, the old, flat land, the lack of a unified whole, lack of style. (2) The place of the city in Young Estonia’s texts. Though in earlier publications there were only a few passing references to urban culture, the problems of the city come to the fore in several programmatic texts and in the visual design of the fourth Young Estonia album in 1912. By then the core members of Young Estonia also had had real experience of a large metropolis. If their earlier attitude toward the city had been critical, then in these Young Estonian texts the city finds its positive face. (3) Industry and the proletariat. The Young Estonia movement received stimulus from such general phenomena as factories, technology, and industry. In their imagination working people and educated people seem to live in separate worlds, with different wishes and needs. However, the freedom of the educated would be impossible without political freedom. Although they believed that technological development was a precondition for the creation of urban culture, neither their own literary works nor their other aspirations bore this out. (4) Futurism and film. Young Estonia’s later period coincided with the intensive use of term ”futurism” in Estonian journalism. Young Estonia’s own relations with futurism are contradictory. Young Estonians of the younger generations such as Johannes Semper and Johannes Barbarus were among the first serious popularizers of futurism, while older members of the movement maintained a skeptical distance, especially after the outbreak of the First World War. Few traces of film can be found in the entire decade of Young Estonia’s activities: at that time in Estonia, film was not yet considered to belong to the realm of art. The Young Estonians’ totally negative attitude toward film is significant for that very reason: for them film was a pejorative form of public amusement. The considerable internal diversity of views and tastes in the Young Estonia movement must also be kept in mind: Gustav Suits was interested in Marxism, but regarded culture as an autonomous sphere, not subjected to full economic determinism. Friedebert Tuglas and Bernhard Linde were fascinated by urban culture to some extent, but they do not go very far in that direction. Johannes Aavik’s views seem to follow (perhaps unconsciously) a parallel trajectory to the development of early 20th century urban culture, including futurism and constructivism. Radical new developments are regarded most positively by the young writers Semper and Barbarus, who joined the movement at a later stage. Because of the youth of Estonian culture, The Young Estonians’ rhetorical arsenal does not include full-fledged repertoire of cultural ridicule and rebellion: in such a fledgling culture, there is not yet much of anything to mock.